52 Impact of ERAS program implementation in gynecologic surgery on healthcare costs. (18th September 2019) - Harrison, R; Li, Y; Guzman, A; Pitcher, B; Rodriguez-Restrepo, A; Cain, K; Iniesta, MD; Lasala, JD; Ramirez, PT; Meyer, LA
Abstract : Objectives: To evaluate differences in hospital charges and healthcare service utilization for gynecologic surgery patients managed before and after ERAS implementation. Methods: We retrospectively reviewed women undergoing open gynecologic surgery before and after ERAS implementation. Consecutive patients from 5/2014–10/2014 and 11/2014–11/2015 comprised the pre-ERAS and ERAS cohorts, respectively. Patients were excluded if they had a multidisciplinary surgical team or underwent minimally invasive surgery. All technical and professional charges were ascertained for healthcare services from procedure date until postoperative day 30. Adjuvant treatment charges were excluded. Charges were categorized by the type of clinical service provided. The primary outcome was the difference in total charges between the two groups. Results: A total of 271 patients were included with 58 and 213 patients in the pre-ERAS and ERAS cohort, respectively. 70, 177 technical charges and 6, 775 professional charges were identified and classified. The median hospital charge decreased 15.6% from the pre-ERAS to ERAS groups [95% CI 0–39%; p=0.008]. ERAS patients had lower charges for laboratory services [20% decrease; 95% CI 0–39%; p=0.04], pharmacy services [30% decrease; 95% CI 14–41%; p<0.001], room-and-board [25% decrease; 95% CI 20–47%; p=0.005], and material goods [64% decrease; 95% CI 44–81%; p < 0.001]. No differences in charges were observed for perioperative services, diagnostic procedures, emergency department care, transfusion-related services, interventional radiology procedures, physical/occupational therapy, or outpatient care. Conclusions: Hospital charges and healthcare service utilization were lower for ERAS patients compared with patients receiving conventional perioperative care. ERAS may be considered high value as it provides improved outcomes while lowering resource utilization.